Understanding corruption how corruption works in practice - Barrington, Robert; Dávid-Barrett, Elizabeth; Power, Sam; Hough, Dan (Agenda Publishing, 2022)
Corruption is known to be a complex problem, and understanding corruption in its many forms and global reach is the work of many years. This books tells the story of how corruption happens in practice, illustrated through detailed case studies of the many different types of corruption that span the globe"--Amazon.